Comment on “The ideological background of ancient Chinese clothing culture” - Ruixiang Ji (Trans/Form/Ação)
Commented article: ZHANG, B.; YANG, P. The ideological background of ancient Chinese clothing culture. Trans/Form/Ação: Unesp journal of philosophy, Marília, v. 47, n. 4, “Eastern thought”, e0240061, 2024. Available at: https://revistas.marilia.unesp.br/index.php/transformacao/article/view/14773.